2016
DOI: 10.1002/1873-3468.12440
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of Arabidopsis thaliana transcriptomics reveals intuitive splicing mechanism for circular RNA

Abstract: A new regulatory class of small endogenous RNAs called circular RNAs (circRNAs) has been described as miRNA sponges in animals. Using 16 Arabidopsis thaliana RNA-Seq data sets, we identified 803 circRNAs in RNase R-/non-RNase R-treated samples. The results revealed the following features: Canonical and noncanonical splicing can generate circRNAs; chloroplasts are a hotspot for circRNA generation; furthermore, limited complementary sequences exist not only in introns, but also in the sequences flanking splice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 23 publications
7
59
0
Order By: Relevance
“…Recently, with the development of high‐throughput sequencing and bioinformatics, a huge number of circRNAs have been identified in Archaea, Caenorhabditis elegans , mice, and humans (Danan et al ; Salzman et al , 2012b, Memczak et al , Zhang et al ). Although circRNAs in plants have been identified (Wang et al , Lu et al , Sun et al ), the studies were relatively limited and the molecular functions of circRNAs need further study. In tomato, circRNAs have only been identified in ‘Rui Xin’ fruit under chilling injury (Zuo et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the development of high‐throughput sequencing and bioinformatics, a huge number of circRNAs have been identified in Archaea, Caenorhabditis elegans , mice, and humans (Danan et al ; Salzman et al , 2012b, Memczak et al , Zhang et al ). Although circRNAs in plants have been identified (Wang et al , Lu et al , Sun et al ), the studies were relatively limited and the molecular functions of circRNAs need further study. In tomato, circRNAs have only been identified in ‘Rui Xin’ fruit under chilling injury (Zuo et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary conservation of circRNAs circRNAs are present in most organisms, including Archaea, plants, yeast, and most metazoans (Danan et al, 2012;Wang et al, 2014;Broadbent et al, 2015;Lu et al, 2015;Sun et al, 2016;Ji et al, 2019). However, it is not clear how they have evolved, as they seem to be produced by different mechanisms.…”
Section: Circrna Properties and Featuresmentioning
confidence: 99%
“…These complementary sequences were short, ranging in size from 4 to 5 nucleotides (Table ). Similarly, in Arabidopsis thaliana samples, only 37% of the circRNA had some complementary sequences near the splice sites . These observations indicate that in addition to complementary sequences, there must exist other elements that guarantee circularization.…”
Section: Discussionmentioning
confidence: 95%
“…With the advent of high‐throughput sequencing of nonpolyadenylated RNA transcripts, many studies have revealed large numbers of circRNA that are endogenous to eukaryotes (e.g. humans, mice, zebrafish, worms, fruit flies, plants), many of which are abundant and stable . CircRNA have no free 3′ or 5′ end, so these RNA cannot be detected by molecular techniques that rely on polyadenylated free RNA ends.…”
mentioning
confidence: 99%